Methodological strategies to gain insights into informality and emergence in construction project case studies - Barrett, P.; Sutrisna, Monty (Rjoutledge, 2009)
In investigating complex situations, such as construction projects, the case study approach has been considered reliable to capture rich information for the purpose of the investigation by allowing the investigators to retain the holistic and meaningful characteristics of real-life events. Subsequent to data capture, data analysis will take place according to the intended research methodology. However, there is a potential for certain information to be hidden within the data and diluted during this data analysis phase. In order to minimize this and to reveal informal aspects and freshly emerging themes from the case study data, it is proposed that there is great value in analysing case studies on various levels, through different phases using multiple methods. Examples of the outcomes of applying multiple analyses involving different approaches, such as grounded theory methodology, rich picture diagrams and cognitive mapping, to the same set of data from multiple case studies are presented and discussed. This application of multiple analyses to case study research of construction projects provides valuable insights by revealing informal aspects and stimulating the emergence of a fresh understanding of the processes and interactions among different stakeholders. From the findings, the limits of the formal management systems were revealed. Further, the limits of tacit understanding around an evolving shared vision for a project were found to be substantial dimensions in understanding construction projects in a more holistic way.